Safety, tolerability, and pharmacokinetics/pharmacodynamics of JMT103 in patients with bone metastases from solid tumors - Liang, Xu; Xue, Junli; Ge, Xiaoxiao; Li, Jin; Li, Huiping; Xue, Liqiong; Di, Lijun; Tang, Wenbo; Song, Guohong; Li, Qun; Jiang, Hanfang; Zhao, Wei; et al. (Frontiers in Oncology, 2022)
Bone metastases are common complications of solid tumors. The outcome is poor despite major progress in cancer therapies. We describe a multicenter, open-label, phase 1, dose escalation and expansion trial of JMT103, a novel fully humanized receptor activator of nuclear factor kappa-B ligand (RANKL)-targeting monoclonal antibody, in adults with bone metastases from solid tumors. The study assessed the safety, tolerability, and pharmacokinetics/pharmacodynamics of JMT103. Patients received JMT103 at doses of 0.5, 1.0, 2.0, and 3.0 mg/kg every 4 weeks for 3 cycles. Among 59 patients enrolled, 20 and 39 patients participated in the dose-escalation and dose-expansion phases, respectively. One dose-limiting toxicity was observed at 2.0 mg/kg. The maximum tolerated dose was not determined. Treatment-related adverse events were reported in 29 (49.2%) patients, most commonly hypophosphatemia (30.5%), hypocalcemia (23.7%), and hypermagnesemia (10.2%). No treatment-related serious adverse events were reported. Two patients died due to disease progression, which were attributed to gastric cancer and lung neoplasm malignant respectively. Dose proportionality occurred between exposure levels and administered dose was within a dose range of 0.5 to 3.0 mg/kg. The suppression of urinary N-telopeptide corrected for creatinine was rapid, significant, and sustained across all doses of JMT103, with the median change from baseline ranging from –61.4% to –92.2% at day 141. JMT103 was well tolerated in patients with bone metastases from solid tumors, with a manageable safety profile. Bone antiresorptive activity shows the potential of JMT103 for treatment of bone metastases from solid tumors.